Global, regional, and national burden of decubitus ulcers, 1990–2021: analysis of the current situation, multidimensional analysis, and trend forecasting for the global burden of disease study 2021 - Jing, Zhaoyi; Song, Qingyu; Wang, Bingbing; Ding, Xiao; Yan, Wei; Qi, Xianghua (Frontiers in Medicine, 2025)
BackgroundThis study aimed to deepen the understanding and assessment of the global burden of decubitus ulcers to provide evidence for policy making and resource allocation.MethodsUsing the standardized methodology of the 2021 Global Burden of Disease study, the disease burden of decubitus ulcers was analyzed at the global, regional, and national levels, with a focus on age and gender factors. The study also included health inequality analysis, decomposition analysis, and frontier analysis. The disease burden of decubitus ulcers for the year 2035 was projected.ResultsFrom 1900 to 2021, the incidence, prevalence, and mortality of decubitus ulcers increased continuously. When analyzed by Socio-demographic Index (SDI), incidence decreased slightly in high-SDI regions but increased in all other regions. India was found to bear the heaviest burden of mortality and disability-adjusted life-years (DALYs), while the United States had the highest incidence and prevalence. Health inequality persisted, with the level of inequality in DALYs showing a greater increase compared to 1990. Decomposition analysis indicated that population aging and population growth remained the primary drivers of the increased burden of decubitus ulcers, with some regional variations. Frontier analysis revealed that countries positioned on the disease burden frontier were primarily located in middle-high and high SDI regions.ConclusionThe burden of decubitus ulcers remains substantial globally, with marked disparities across regions and nations. A disproportionately high share of this burden affects older adult populations. Implementation of targeted health policies is warranted to mitigate the global burden of decubitus ulcers.